Messenger by moonlight [large type] : a novel - Whitson, Stephanie Grace (Thorndike Press Large Print, 2016)
Orphaned Annie Paxton and her brothers may have lost the only home they've ever known, but they're determined to make a better future in St. Joseph, Missouri. Annie dreams of a pretty house with window boxes, and having friends, and attending church every week. But then her brothers spot the ad for a new venture called the Pony Express. "Wanted," it reads, "Young, skinny fellows not over eighteen. Must be expert riders and willing to risk death daily. Orphans preferred." Sure enough, both her brothers land jobs as Express messengers, and Annie puts her dreams on hold to work as a cook at Clearwater Ranch, a station along the Pony Express route. Annie struggles to adapt to her new job -- work made all the more challenging when she has so many to feed and few ingredients. The gruff station owner, George, doesn't seem inclined to make her life any easier, or at least not at first. But slowly a friendship builds between them. When Annie attracts the attention of a refined, dashing lieutenant from the nearby fort, she'll have to learn how to trust her instincts and follow her heart, even if she's conflicted about which way it's leading her.